2017
DOI: 10.1007/s00216-017-0603-4
|View full text |Cite
|
Sign up to set email alerts
|

Apparent activation energies of protein–protein complex dissociation in the gas–phase determined by electrospray mass spectrometry

Abstract: We have developed a method to determine apparent activation energies of dissociation for ionized protein-protein complexes in the gas phase using electrospray ionization mass spectrometry following the Rice-Ramsperger-Kassel-Marcus quasi-equilibrium theory. Protein-protein complexes were formed in solution, transferred into the gas phase, and separated from excess free protein by ion mobility filtering. Afterwards, complex disassembly was initiated by collision-induced dissociation with step-wise increasing en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Well-resolved spectra showed that the protein exists both as a monomer and a dimer ( Figures 1 A and 1B). The relative abundance of monomer/dimer was ∼5:95, suggesting a strong dimer interface ( Yefremova et al., 2017 ). The spectra also revealed the binding of two adduct molecules (measured mass: 775 ± 50 Da) to the UapAG411V Δ1-11 dimer.…”
Section: Resultsmentioning
confidence: 99%
“…Well-resolved spectra showed that the protein exists both as a monomer and a dimer ( Figures 1 A and 1B). The relative abundance of monomer/dimer was ∼5:95, suggesting a strong dimer interface ( Yefremova et al., 2017 ). The spectra also revealed the binding of two adduct molecules (measured mass: 775 ± 50 Da) to the UapAG411V Δ1-11 dimer.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated how insight into the structural changes that SOD1 undergoes upon gas phase activation, highlighting how both bond breakage and formation pay a role in governing the trajectory taken and the products observed. We have presented an Arrhenius-type framework for analysis which, despite assumptions implicit therein and together with other recently presented methodologies 58 , represents a means for meaningful and direct comparison between proteins in terms of the barriers on the free energy landscape. This work therefore represents a step towards maximising the utility of information extracted from native MS experiments where the protein folding funnel is explored by deliberate gas phase activation 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, from ESI-MS ETD studies of multiply charged myoglobin gas phase ions it was concluded that—depending on the complexes´ charge states—the heme group might be coordinated by one of two histidinyl residues, mainly by His93 but also by His64, or by both, suggesting some similarity between in-solution and gas phase complex structures—at least around the heme binding pocket [ 25 ]. The existence of relatively defined macromolecular structures during the heme dissociation process (e.g., as transition state) fits our model, so we postulate that dissociation of immune complexes follows in principle a hard spheres model, i.e., entropy contributions at the transition state are small [ 14 ]. In fact, in-solution antibody—antigen interactions are enthalpy-driven [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 64%
“…The uncertainty of this method has been estimated to be approx. 10% [ 14 ]. Hence, myoglobin is considered to be an adequate standard for developing the ESI-MS method by which protein-ligand dissociation reactions may be studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation